Activity of nucleoside triphosphate diphosphohydrolase, 5′-nucleotidase, and adenosine deaminase in cattle fed on pastures treated with different nitrogen fertilizers. Issue 5 (3rd July 2017) - Favero, Juscivete Fátima; Christ, Ricardo; Gabriel, Mateus Eloir; Henker, Luan Cleber; Stedille, Fernanda Agustini; Piva, Manoela Marchezan; Bottari, Nathieli Bianchin; Schetinger, Maria Rosa Chitolina; Morsch, Vera Maria; Baldissera, Matheus Dellaméa; da Silva, Antonio Waldimir Leopoldino; Mendes, Ricardo Evandro; et al.
ABSTRACT: The aim of this study was to evaluate nucleoside triphosphate diphosphohydrolase, 5′-nucleotidase, and adenosine deaminase activities in cattle fed on cuttings from pastures fertilized with urea compared to animals fed on cuttings from organically fertilized or from non-fertilized pastures. Blood samples were collected up to 9 h after feeding, and nitrite and enzyme activities were evaluated. The animals feeding on urea-fertilized pasture suffered subclinical intoxication. Serum nitrite levels increased by about 50% and adenosine deaminase activity increased almost sixfold 4 and 6 h after feeding on urea-fertilized pasture, and adenosine deaminase in platelets almost doubled 6 and 9 h after feeding. In platelets, nucleoside triphosphate diphosphohydrolase activity with adenosine triphosphate as substrate increased 2, 4, 6 and 9 h after feeding while nucleoside triphosphate diphosphohydrolase with adenosine diphosphate as substrate and 5′-nucleotidase activities increased only 9 h after feeding. Increased activities of these enzymes may be implicated in the pathophysiology of subclinical intoxication since they are involved in many biochemical functions.